ARTIFICIAL MATURATION: INCREASE THE SPEED OF GONAD MATURATION, EGGS QUALITY AND PRODUCTIVITY OF CLIMBING PERCH (Anabas testudineus Bloch) - Prihardianto, Raditya Wahyu; Garnama, Rangga; Kesuma, Rudy Angga; Nurjanah, Lilis (Program Kreativitas Mahasiswa - Penelitian, 2013)
Climbing perch (Anabas testudineus, Bloch) is one of freshwater fishes having the potential to be developed as it has a fairly high economic value. Culture of climbing perch in Indonesia is still under developed because of some barriers that occur in the culture system such as the availability of seed, broodstock rematuration requires long time about three months and influenced by the season.Â  Application of egg stimulant that having complete substances may support climbing perch productivity in terms of increasing egg production, shorter time to mature, and improving eggs quality. This research was aimed to gain techniques and effective egg stimulant dose to produce good quality eggs. Doses of eggs stimulant used were 1 g/kg, 2 g/kg, 3 g/kg diet, without eggs stimulant (control) and control+starch. Fish were reared for 45 days (up to mature egg) and fed twice a day. Â The results showed that eggs stimulant dose of 1 g/kg diet allowed best gonad maturation and fastest compared to other treatments and control. Thus, this could be used to accelerate broodstock maturation to support seed production of climbing perch in near future.Keywords: Anabas testudineus, seed production, artificial maturation, egg stimulant